2003
DOI: 10.1051/vetres:2003001
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the lungs of pigs infected with porcine reproductive and respiratory syndrome virus and associations with the production of apoptogenic cytokines

Abstract: -Apoptosis was studied in the lungs of pigs during an infection with a European strain of porcine reproductive and respiratory syndrome virus (PRRSV) and it was examined if cytokines were involved in the induction of apoptosis. Twenty-two 4-to 5-week-old gnotobiotic pigs were inoculated intranasally with 10 6.0 TCID 50 of the Lelystad virus and euthanised between 1 and 52 days post inoculation (PI). The lungs and broncho-alveolar lavage (BAL) cells were assessed both for virus replication and apoptosis; BAL fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 34 publications
6
79
1
Order By: Relevance
“…For example, virus concentration in serum and BAL were significantly related at 21 dpi, but not at 10 dpi, where virus levels were substantially greater, suggesting different time trends for the virus dynamics at different locations. Indeed, viral loads in serum are reported to peak as early as 4 dpi (Greiner et al, 2000), whereas virus load in the lung peaks at 7 to 9 dpi (Labarque et al, 2003). However, Petry et al (2005) found moderately strong positive correlations between virus concentrations in blood, lung, and lymph nodes at 14 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…For example, virus concentration in serum and BAL were significantly related at 21 dpi, but not at 10 dpi, where virus levels were substantially greater, suggesting different time trends for the virus dynamics at different locations. Indeed, viral loads in serum are reported to peak as early as 4 dpi (Greiner et al, 2000), whereas virus load in the lung peaks at 7 to 9 dpi (Labarque et al, 2003). However, Petry et al (2005) found moderately strong positive correlations between virus concentrations in blood, lung, and lymph nodes at 14 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…These include apoptosis of infected cells, apoptotic death of proximate non-infected cells, induction of inflammatory cytokines, induction of polyclonal B cell activation, and reduction in the bacterial phagocytosis and killing by macrophages that result in increased susceptibility to septicaemia (Lemke et al 2004, Butler et al 2007, Zimmerman et al 2012. The cause of PRRSV-induced indirect apoptosis is unknown, but is probably due to substances released from, or secreted by, infected macrophages -apoptotic cytokines, reactive oxygen species (ROS) or nitric oxide (Chiou et al 2000, Choi et al 2002, Labarque et al 2003. In primary bovine turbinate cells infected with bovine viral diarrhoea virus (BVDV) oxidative stress was suggested to be a crucial event in the sequence leading to apoptotic cell death (Schweizer and Peterhans 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of TNF-α and IL-10 immunostained cells showed an increase in LV and SU1-bel groups. Previous studies have reported an association between apoptosis in the lungs, lymphoid tissues and the expression of several cytokines, such as IL-1, IL-10, IL-6, TNF-α and TGF-ÎČ, suggesting a mechanism for cytokine induced apoptosis in PRRSV infection (Choi et al, 2002;Labarque et al, 2003;RodrĂ­guez-GĂłmez et al, 2014). The results herein with the higher counts for apoptotic cells rather than PRRSV-positive cells point towards a strain-dependent behaviour in the induction of apoptosis and reinforce the hypotheses of both PRRSV-induced apoptosis and indirect mechanisms involved in the induction of apoptosis during PRRSV infection (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…and has been suggested to play a significant role in PRRSV infection, with increased apoptotic cells widely distributed within both PRRSV-1 and PRRSV-2 infected tissues (Feng et al, 2002;Labarque et al, 2003;Wang et al, 2011;GĂłmez-Laguna et al, 2012;He et al, 2012;Li et al, 2014;Morgan et al, 2014;RodrĂ­guez-GĂłmez et al, 2014).…”
Section: Apoptosis Of Immune Cells Can Be Involved In the Immunopathomentioning
confidence: 99%
See 1 more Smart Citation